Chicken RAPS: Chicken Robot-assisted Pyeloplasty Simulation. Validation Study of a Novel Chicken Model for Wet Laboratory Training in Robot-assisted Pyeloplasty - Nikolaos Liakos; Rudolf Moritz; Sami-Ramzi Leyh-Bannurah; Özlem Güner; Jörn H. Witt; Christian Wagner (European Urology Open Science, 2022)
Background: Since the introduction of minimally invasive surgery, the number of simulation models available for teaching new surgeons has continued to increase. Objective: To evaluate and validate use of a model for teaching robot-assisted pyeloplasty. Design, setting, and participants: Twenty simulated robot-assisted pyeloplasty procedures were performed by experienced (n = 4) and novice (n = 16) surgeons using a chicken crop model at two different training centers using third- and fourth-generation robotic systems. Outcome measurements and statistical analysis: We evaluated the time needed to perform the procedure, and the sufficiency and patency of the anastomosis. Participants rated the efficiency, face validity, and possible acceptance of the model as part of a structured curriculum on a scale from 0 to10. Statistical significance for comparison of results was set at p < 0.05. Results and limitations: Robot-assisted pyeloplasty was successfully performed by 75% of the participants. The completion time was significantly higher in the novice group (p = 0.016). The model was deemed to be similar to the human ureteropelvic junction by the novice group. Both groups regarded the model as a useful simulation task as part of a standardized training curriculum, with mean scores of 6.5 versus 8.69 (p = 0.046) for face validity and 8 versus 9.25 for acceptance (p = 0.053) reported by the experienced versus novice group, respectively. Limitations of the study are the costs associated with the robotic system and the unequal number of participants in the groups. Conclusions: The chicken crop model is a low-cost and reproducible simulation model for accomplishing both the resection and reconstructive steps during the learning phase for robot-assisted pyeloplasty. Patient summary: We assessed the use of chickens as a model for practicing a robot-assisted operation called pyeloplasty to fix narrowing of the ureter (the tube that drains urine from the kidney to the bladder) where it attaches to the kidney. This model can be used for simulation of robot-assisted pyeloplasty when training new robotic surgeons.